Tren Riset Hamidulloh Ibda tentang Pendidikan Dasar Islam: Kajian Literatur Sistematis Dengan Open Knowledge Maps - Dian Marta Wijayanti; Andrian Gandi Wijanarko (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
Several kinds of literature have examined Hamidulloh Ibda's thoughts, research, or articles, but those focusing on research trends in basic Islamic education with systematic literature review methods are minimal. This research method applies a systematic literature review and PRISMA protocol with the main database Open Knowledge Maps. Qualitative data analysis was assisted by the Open Knowledge Maps application and Publish or Perish 7. The results of searching for articles through the Open Knowledge Maps application were 44. Of the 44 articles, 2 articles were discarded because they were the same, and 3 were discarded because of other people's work, leaving 39 articles used as systematic literature reviews. The findings of Hamidulloh Ibda's research trends based on Open Knowledge Maps visual mapping are 15 themes. The qualifications of journals that publish Hamidulloh Ibda's work from indexation are Scopus Q3 (1 issue), Sinta 2 (6 issues), Sinta 3 (9 issues), Sinta 4 (12 issues), Sinta 5 (7 issues), and journals not indexed by Sinta (4 issues). Meanwhile, in terms of journal scale, there are 1 reputable international journal, 7 international journals, and 31 national journals. The impact factor of 39 articles by Hamidulloh Ibda taken from Publish or Perish 7 data is taken from the top 10 articles based on rank, there are 4 articles, namely in article number 4 (rank 6/50 citations), number 5 (rank 2/189 citations), number 9 (rank 9/32 citations), and number 33 (rank 10/17 citations). Hamidulloh Ibda's research found 22 articles relevant to Islamic basic education, while 17 articles were irrelevant. Future research needs to be conducted to examine researchers, research groups, or research communities on certain themes in depth.